Unlocking the Complete Chloroplast Genome of a Native Tree Species from the Amazon Basin, Capirona (Calycophyllum spruceanum Benth., Rubiaceae), and Its Comparative Analysis with Other Ixoroideae Species - Saldaña Serrano, Carla Lizet (2021)
16 páginas